How do doctors manage physical activity advocacy for patients and their own self-care? A qualitative interview study of general practitioners in Ireland - Andrew O'Regan; Vikram Niranjan; Amanda Clifford; Joe MacDonagh; Ibak Baky; Alison Bourke; Conor Byrne (BMJ Open)
Objectives This study explored general practitioners’ (GPs) understanding of physical activity advocacy to patients and their own self-care, how GPs perceive their own physical activity behaviours, how their personal experience of physical activity affects how they promote it in practice and how they define the limitations of their role in this.Design A qualitative design, involving online semi-structured interviews, was employed. Data was analysed by an interdisciplinary team of researchers using an inductive thematic approach.Setting and participants Participants were GPs (n=21) and were recruited from an education and research network.Findings A single meta-theme was identified—moving towards more physically active lifestyles through the art of medicine—with three related subthemes. Subthemes relate to how GPs determine the extent of their role and responsibilities, how physical activity promotion is adapted to the context and how ‘what I’ say is not necessarily ‘what I do’. After many consultations, mutual trust can develop when the GP’s role is clarified, and the GP can educate and support the initiation and maintenance of physical activity behavioural change by sharing personal experiences of physical activity behaviour.Conclusion Based on personal experience and enduring relationships with their patients, GPs are in a unique position to discuss appropriate physical activity with their patients and perform an important role in explaining and gaining access to physical activity for their patients. Support in the form of community-based resources and programmes as well as brief intervention skills could enhance GP ability to further promote physical activity.